Parametric architecture in it’s second phase of evolution - Heidari, A.; Sahebzadeh, S.; Sadeghfar, M.; Taghvaei, B. Erfanian (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper seeks to illustrate the evolution history of Parametric Architecture and describe the reasons why parametric architecture, in its second phase of evolution, called “Parametricism 2.0”, is showing promising abilities in solving more and more intricate socio-environmental problems. In this sense, paper discusses that mentioned school of architecture can be used in several fields other than mere form finding and geometrical coding. Current article studies the history of parametric architecture by finding the root of its name, reviewing its early designs and discussing the work of two of its precursors; then moves on to examine the current situation of the style and defines the word: Parametricism. Paper continues to study the vistas ahead by presenting techniques that empower Parametricism and concludes its discussion by presenting a redefinition for Parametricism. Overall, the paper depicts how “Parametricism 2.0” intends to go back to solving socio-environmental problems; Problems that all the existing evolutionary and generative techniques were initially designed in order to answer them.